The Relationship of Farmers Characteristics and Perception of the Occupational Health and Safety (OHS) Application in Farming Activities in Wonosalam District, Jombang Regency, East Java - Farid, Abdul; Pratiwi, Arum; Fitri, Aan Dwi Auliya (Sodality: Jurnal Sosiologi Pedesaan, 2019)
The majority of residents of Wonosalam Subdistrict are farmers who are at high risk of having health problems due to interactions with hazardous materials, such as pesticides. The implementation of occupational safety and health (K3) which is still low triggers the occurrence of accidents and diseases in farmers that have an impact on performance degradation so that it can cause losses. The aim of this study to find out the relationship between farmers 'characteristics and farmers' perceptions in the application of K3 in Wonosalam District, Jombang Regency by using descriptive quantitative methods. Observation variables include age, level of education, training, length of farming, income, land status and land area on perceptions of OHS application. The data used are primary data obtained from 98 farmers using a questionnaire. Analysis of the data used in this study is thecorrelation analysis Spearman Rank. The results showed that the characteristics of farmers associated with farmers' perceptions in applying OSH were the level of education and training. While the characteristics of farmers who are not related to the perception of farmers in the application of OSH are age, length of farming, income, land status and land area.